Development and evaluation of a surgical skills lab for trainee surgeons: a 10-year experience at the Münster University Hospital - Annika Mohr; Jens Peter Hölzen; Sandra Stöppeler; Hans-Ullrich Spiegel; Daniel Palmes; Ralf Bahde; Linus Kebschull; Mazen A. Juratli; Benjamin Strücker; Andreas Pascher; Felix Becker (BMC Medical Education)
Abstract Background Surgical training persists of intensive work, incessant practice, and, most importantly, experience. Owing to the changing surgical environment, increasing specialization, and rapid development of minimally invasive techniques, new innovative approaches in surgical training are necessary to achieve excellent postgraduate education. Here, we introduce a surgical skills lab that offers a multi-course program featuring a concise, modular curriculum comprising well-defined and simple-to-follow procedures, progressively moving surgical techniques from ex vivo to in vivo settings. The evaluation of the course was conducted by analyzing the participants’ self-assessment before and after the course. Methods Over the time of ten years, we conducted one-day surgical training courses covering basic surgical techniques, gastrointestinal anastomosis, visceral resection techniques, and techniques in vascular surgery with a total of 348 participants. To assess differences in the self-evaluation of surgical skills before and after each course, a questionnaire (non-validated self-report 5-point Likert scale) was administered to each participant. Results were analyzed with t-test for paired samples. Results Before the course, most participants had no practical knowledge of most exercises, and major help was needed. However, after training, the majority of participants were able to perform the surgical techniques independently with little or no assistance. Moreover, a statistical analysis comparing pre- and post-course self-assessment scores for surgical skills revealed significant improvements (p < 0.05) after the course. Conclusion During the one-day course, it was possible to teach and perform diverse surgical procedures under the guidance of experienced surgeons. The independent reproducibility of the learned material after the course is not yet known, therefore, further investigation is necessary to provide additional information to improve the program. However, with this step-by-step training, we were able to conduct a successful teaching program, shown by the fact that the participants showed significant improvement. Thus, the training presented in this study can serve as a guide for teaching surgical skills outside of the operating room.